Retinal vessel morphology in rheumatoid arthritis: Association with systemic inflammation, subclinical atherosclerosis, and cardiovascular risk. (6th November 2017) - Anyfanti, Panagiota; Triantafyllou, Areti; Gkaliagkousi, Eugenia; Koletsos, Nikolaos; Athanasopoulos, Georgios; Zabulis, Xenophon; Galanopoulou, Vasiliki; Aslanidis, Spyros; Douma, Stella
Abstract: Objective: Quantification of retinal vessel morphology has emerged as a marker of cardiovascular health. We examined retinal microvascular diameters in RA, particularly in regard to systemic inflammation, subclinical atherosclerosis, and cardiovascular risk. Methods: Retinal images from RA patients and controls were processed using computerized software, to obtain CRAE and CRVE and AVR. Subclinical atherosclerosis was assessed with cIMT, and 10‐year risk of general cardiovascular disease was calculated. Results: Both CRAE (78.8 ± 8.9 vs 90.2 ± 9.9 μm, P  < .001) and AVR (0.69 ± 0.09 vs 0.81 ± 0.09, P  < .001) were decreased in RA patients (n = 87) compared to controls (n = 46), whereas CRVE did not differ. Among RA patients, CRAE and AVR were inversely associated with both cIMT and CRP, whereas CRVE positively correlated with CRP ( P  < .05 for all). CRAE additionally correlated with cardiovascular risk score ( r  = −.396, P  = .001). In the multivariate analysis, cardiovascular risk was associated with CRAE; age with CRVE, while CRP independently predicted AVR. Conclusions: Our study shows altered retinal microvascular morphology in RA patients. Inflammation appears as the biological link for the observed association between retinal microvascular abnormalities and subclinical atherosclerosis. Retinal arteriolar narrowing might play its own role in cardiovascular risk prediction in RA.